Diagnosis of Pulmonary Hypertension Using Ultrasonography in the Management of Critical Patients in the Intensive Care Unit - Eka Adhiany; Muhammad Iqbal (Budapest International Research in Exact Sciences (BirEx) Journal, 2020)
Pulmonary arterial hypertension is most often diagnosed in its advanced stages because of the nonspecific nature of early symptoms and signs. Although clinical assessment is essential when evaluating patients with suspected pulmonary arterial hypertension, echocardiography is a key screening tool in the diagnostic algorithm. Echocardiography is valuable in assessing prognosis and treatment options, monitoring the efficacy of specific therapeutic interventions, and detecting the preclinical stages of disease. In this report, we reported A 35 years old woman admitted to the emergency unit with breathing difficulty which has felt since 2 days before. she transferred from rural hospital after hospitalized for a week. The patient has history of spinal surgery due to spondylitis tuberculosis 8 months ago and has an anti-tuberculosis drug for 2 months. The vital signs show respiratory failure with blood pressure 114/70 mmHg, heart rate 118 bpm, respiratory rate 35-40 bpm and pulse saturation 80-85% with non-rebreathing mask. Physical examination shows increasing work of breathing, without rales and wheezing, liver enlargement palpated 3 fingers below right ribs the chest x ray shows cardiomegaly and right pleural effusion